ALTERNATIVE VERSIONS OF PERIODIC SYSTEM OF CHEMICAL ELEMENTS IN THE EDUCATIONAL PROCESS - Oleg V. Mikhailov (Высшее образование в России)
The article addresses the problems relating to the use of the alternative periodic tables of chemical elements in studying of various chemical disciplines. The versions concerned are the so-called «short-form" table proposed by Dmitri Mendeleev and «long-periodic table » proposed by A. Werner and recommended by the International Union of Pure and Applied Chemistry (IUPAC). The advantages and disadvantages both of these variants have been shown. It has been noted that now in the Russian chemical education it is mainly used a "short-periodical» version. The author proposes a modification of the table version of the periodic table of chemical elements designed to overcome the disadvantages of the two most common variants now interpreting the periodic law of Dmitri Mendeleev, which may be used in the educational process.